1999
DOI: 10.1099/00222615-48-1-89
|View full text |Cite
|
Sign up to set email alerts
|

Oligofructose contributes to the protective role of bifidobacteria in experimental necrotising enterocolitis in quails

Abstract: Bifidobacteria are dominant in the gut of full-term infants, although colonisation by them is often delayed in preterm neonates. Bifidobacteria are recognised to have beneficial effects on digestive disorders and they might prevent neonatal necrotising enterocolitis (NEC), a gastrointestinal disease that predominantly affects premature infants. They have been shown to protect gnotobiotic quails against NEC-like lesions when the birds were inoculated with faecal flora from preterm infants, decreasing the clostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Several strategies for the prevention of NEC have been proposed including delaying of the initiation of feeding, 28,29 minimal enteral feeding regimens, 29,30 dietary supplements including egg phospholipid, 31 lactobacillus, 32,33 oligofructose, 34 and the administration of immunoglobulin G-immunoglobulin A. 35 Although these strategies may reduce the incidence of NEC, they do so at the expense of increasing LOS 36 and incurring costs for administering preventive dietary supplements unnecessarily to infants who do not go on to develop NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies for the prevention of NEC have been proposed including delaying of the initiation of feeding, 28,29 minimal enteral feeding regimens, 29,30 dietary supplements including egg phospholipid, 31 lactobacillus, 32,33 oligofructose, 34 and the administration of immunoglobulin G-immunoglobulin A. 35 Although these strategies may reduce the incidence of NEC, they do so at the expense of increasing LOS 36 and incurring costs for administering preventive dietary supplements unnecessarily to infants who do not go on to develop NEC.…”
Section: Discussionmentioning
confidence: 99%
“…enteropathogenic Escherichia coli and Campylobacter jejuni (9, 10). In addition, several studies have demonstrated that consumption of certain oligosaccharides can increase the endogenous bifidobacteria level in the intestine (11,12 …”
mentioning
confidence: 99%
“…The use of oligofructose could help prevent the overgrowth of bacteria implicated in necrotising enterocolitis (7). Cresci et al (8) showed in rats that a high starch diet modi ed the composition of faecal ora (prevalence of clostridia) and altered the faecal concentration of short chain fatty acids (SCFA).…”
Section: Dietary Carbohydratesmentioning
confidence: 99%